Radial glial cells: Key organisers in CNS development. - Barry, Denis (My University, 2014)
Radial glia are elongated bipolar cells present in the CNS during development. Our understanding of the unique roles these cells play has significantly expanded in the last decade. Historically, radial glial cells were primarily thought to provide an architectural framework for neuronal migration. Recent research reveals that radial glia play a more dynamic and integrated role in the development of the brain and spinal cord. They represent a major progenitor pool during early development and can give rise to a small population of multipotent cells in neurogenic niches of the adult CNS. Radial glial cells are a heterogeneous population, with divergent and often poorly understood roles across different brain and spinal cord regions during development; this heterogeneity extends to specialised adult subtypes, such as tanycytes, Muller glial cells and Bergman glial cells which possess morphological similarities to radial glial but play distinct functional roles in the CNS.
PUBLISHED
Keywords: Glioma; Neurodevelopment; Neuronal migration; Radial glia; Neuroscience